Multi-step mode signal conversion algorithms in hall sensor devices - Голяка, Роман Любомирович; Готра, Зенон Юрійович; Ільканич, Вікторія Юріївна; Марусенкова, Тетяна Анатоліївна; Лесінський, Валентин Вікторович; Годинюк, Іван Михайлович (Eastern-European Journal of Enterprise Technologies, 2014)
This paper presents a numerical and experimental based data analysis of electromagnetic noise immunity in magnetic field measurement devices on Hall sensor transducers. Relevance of this problem takes place in sensor networks with autonomous low-powered sources, magnetic field mapping devices for charged particle accelerators fusion reactors, etc. The proposed algorithm is based on averaging of several step by step signals, especially, acquired by three consecutive measurements in time interval: (t + dt), (t), (t – dt). In (t + dt) and (t – dt) time intervals a Hall sensor current pulse magnitude and directions are the same. Contrary to these, in (t) time interval the Hall sensor current has the opposite direction. It is shown that the efficiency of triple step measurements is three times higher than in double step measurement. The integral performance criterion concept of the signal converter effectiveness is introduced. The performance criterion factor is defined as a ratio of signal converter electromagnetic noise immunity to its energy consumption. A signal transducer optimized to noise immunity study, its operating modes and Hall sensor parameters are described. Both calculation and experiment results show that the performance criterion factor in triple step measurements is twice higher than in double step measurements.